Quando o êxito do serviço extingue relacionamentos: aplicação do modelo BG/NBD em um curso pré vestibular/ENEM - Marconato, Pedro Henrique Lima (2019)
By aligning greater engagement in strategic, customer-based building with the use of metrics to prove marketing investments, Customer profitability, Customer Equity and Customer Lifetime Value naturally prove to be tools of extreme compatibility with the current marketing landscape. These tools have the ability to derive client behavior by translating it into monetary values and verifying the behavior of the investments made by the marketing area. Obtaining such information gives decision making greater strength and assertiveness, corroborating to the planning and implementation of actions more accurately. In this sense, the present study aimed to apply a Customer Lifetime Value estimation model in the bottom-up mode (individualized by customer), in a sample of clients of the sector preparatory courses for Vestibular / ENEM in the city of Santa Maria. The Beta Geometric Negative Binomial Distribution (BG / NBD) model was applied from the work of Fader, Hardir and Lee (2005b). The results identify a behavior different from normal market patterns within the preparatory course client base, where much of the base is not retained counterintuitive due to the success of the relationship. The applied model showed (1) a satisfactory estimation and prediction capacity; (2) the potential values to be expected in the future for each of its customers; (3) that the customer base has a high dilution over the years and the relationship time decreases the customer contribution potential. The analysis environment, presented by the study, reveals that in markets where the relationship pattern distances itself from normality, there is a need for a closer look at both the researcher and the applied model.